“BAHASA SIMALUNGUN ATAS” CURRENT EXISTENCE AND ITS REVITALIZATION - Willem Saragih (BAHAS, 2015)
There are at least three categories of language in the world wide: local language, national language and international language. Of the three categories, the least attention paid by the government is to its nation’s local languages. This lack of care results in language endangerment which has been the focus of much attention over the past few decades, and as a result a wide range of people are now working to revitalize and maintain local languages. Bahasa Simalungun Atas (BSA), a sub-dialect of Bahasa Simalungun which is used in the upper part of Simalungun territory, is endangered too. Despite the not too many native speakers of the language it is an important asset to Indonesian people as a nation of over six hundred local languages, though. Therefore, the language needs to be revitalized or it will gradually disappear. This paper attempts to provide some information about the situation and condition of Bahasa Simalungun Atas at present so as to draw more attention of the competent parties for its revitalization. For that purpose, current existence of the language, some factors causing the language endangerment, as well as well as how the language can be revitalized are presented. Key Words: language endangerment, Bahasa Simalungun Atas (BSA), existence, revitalization